MINAT BELAJAR DAN LINGKUNGAN KAMPUS SEBAGAI DETERMINASI HASIL BELAJAR MAHASISWA - Rendra Gumilar; Riki Yakub Pirdaus (Mimbar Agama Budaya, 2020)
Abstract The low learning outcomes of Economic Education students is the reason why this research was conducted, so that it will determine the determinants of learning outcomes. The sample of this study was the Economics Education Students of the Teaching and Education Faculty of Siliwangi University, Tasikmalaya class of 2018 with a total of 112 people. The research method in this study was a survey with a rating scale questionnaire data collection tool and data analysis using multiple linear regression techniques using SPSS 25. The results showed interest in learning, the campus environment, and learning outcomes included in the medium category, to influence learning interest and the campus environment significant effect on student learning outcomes by 41.7% and 58.3% influenced by other factors.Abstrak. Rendahnya hasil belajar mahasiswa Pendidikan Ekonomi menjadi alasan mengapa penelitian ini dilakukan, sehingga akan mengetahui faktor determinasi hasil belajar. Sampel penelitian ini adalah Mahasiswa Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan Universitas Siliwangi Tasikmalaya angkatan 2018 dengan jumlahnya 112 orang. Metode penelitian dalam penelitian ini adalah survey dengan alat pengumpul data angket model rating scale dan analisis data menggunakan teknik regresi linier berganda menggunakan SPSS 25. Hasil penelitian menunjukan minat belajar, lingkungan kampus, dan hasil belajar termasuk kategori sedang, untuk pengaruh minat belajar dan lingkungan kampus berpengaruh signifikan terhadap hasil belajar mahasiswa sebesar 41,7% dan 58,3% dipengaruhi oleh faktor lain.